2021
DOI: 10.3390/life11010049
|View full text |Cite
|
Sign up to set email alerts
|

Noncoding RNA: An Insight into Chloroplast and Mitochondrial Gene Expressions

Abstract: Regulation of gene expression in any biological system is a complex process with many checkpoints at the transcriptional, post-transcriptional and translational levels. The control mechanism is mediated by various protein factors, secondary metabolites and a newly included regulatory member, i.e., noncoding RNAs (ncRNAs). It is known that ncRNAs modulate the mRNA or protein profiles of the cell depending on the degree of complementary and context of the microenvironment. In plants, ncRNAs are essential for gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 148 publications
0
15
0
Order By: Relevance
“…Neither of them can encode proteins, and lncRNAs modulate gene expression via multiple mechanisms, including transcriptional initiation, 7 splicing, 8 mRNA stability 9 and translational control. 10 Currently, increasing evidence suggests that lncRNAs represent a key mechanism in biological processes 11 and metabolic diseases, 8 such as diabetes. Genetic and highfat diet (HFD)-induced diabetic mice have a high hepatic expression of the lncRNA maternally expressed gene 3 (MEG3).…”
Section: Introductionmentioning
confidence: 99%
“…Neither of them can encode proteins, and lncRNAs modulate gene expression via multiple mechanisms, including transcriptional initiation, 7 splicing, 8 mRNA stability 9 and translational control. 10 Currently, increasing evidence suggests that lncRNAs represent a key mechanism in biological processes 11 and metabolic diseases, 8 such as diabetes. Genetic and highfat diet (HFD)-induced diabetic mice have a high hepatic expression of the lncRNA maternally expressed gene 3 (MEG3).…”
Section: Introductionmentioning
confidence: 99%
“… 64 However, there is no evidence of the co-occurrence of nuclear-encoded RNA-induced silencing complex (RISC) components in plant chloroplasts. 62 Interestingly, overexpression of long dsRNA molecules in plastomes partially produced unexpected lower molecular weight transcripts than the desired full-length double-stranded structures, suggesting the existence of an active RNA processing mechanism in plastids. 65 , 66 Molecular genetics and transplastomic expression studies suggested that antisense-strand mRNAs of chloroplast rrn5 gene ( AS5 ) formed RNA duplexes with 5S -rRNA precursors which served as apparent dsRNA substrates of plastidial dsRNA-dependent RNase III enzymes.…”
Section: Resultsmentioning
confidence: 99%
“… 5 Numerous small noncoding RNA molecules have been recurrently identified in chloroplasts. 62 However, their involvement in post-transcriptional regulation of plastidial mRNA is still underexplored. Perhaps this is due to the lack of an effective carrier to transport a small RNA molecule into the target organelle to study its function in an organellar RNA suppression mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…Exploiting the newly emerging knowledge of the lncRNA-mitophagy-cancer axis may provide novel targets for cancer therapy. In this review, we will summarize recent progress on the role of lncRNAs in malignancy, demonstrating the importance of mitochondria-associated lncRNAs in cancer metabolism, apoptosis, and mitophagy ( Dong et al, 2017 ; Zhao et al, 2018 ; Anand and Pandi, 2021 ).…”
Section: Introductionmentioning
confidence: 99%